High temperature properties of the monolithic CVD β-SiC materials joined with a pre-sintered MAX phase Ti3SiC2 interlayer via solid-state diffusion bonding. Issue 4 (April 2017) - Tatarko, Peter; Chlup, Zdeněk; Mahajan, Amit; Casalegno, Valentina; Saunders, Theo G.; Dlouhý, Ivo; Reece, Michael J.
Abstract: Monolithic high purity CVD β-SiC materials were successfully joined with a pre-sintered Ti3 SiC2 foil via solid-state diffusion bonding. The initial bending strength of the joints (∼ 220 MPa) did not deteriorate at 1000 °C in vacuum, and the joints retained ∼ 68 % of their initial strength at 1200 °C. Damage accumulation in the interlayer and some plastic deformation of the large Ti3 SiC2 grains were found after testing. The activation energy of the creep deformation in the temperature range of 1000 – 1200 °C in vacuum was ∼ 521 kJmol −1 . During the creep, the linkage of a significant number of microcracks to form a major crack was observed in the interlayer. The Ti3 SiC2 interlayer did not decompose up to 1300 °C in vacuum. A mild and well-localized decomposition of Ti3 SiC2 to TiCx was found on the top surface of the interlayer after the bending test at 1400 °C in vacuum, while the inner part remained intact.